Social Adaptation of Generation Z in Multicultural Workplaces: Evidence from the TIDAYU Context of West Kalimantan - Raziki Waldan; Hamrila Abdul Latip; Siti Aisyah Ya’kob; Zarkasi Zarkasi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
Generation Z has become a dominant workforce cohort, whose expectations for openness, flexibility, and meaningful work often intersect with the multicultural and multigenerational dynamics of local workplaces. This study aims to examine how Generation Z employees in West Kalimantan socially adapt to organizational environments shaped by the interethnic TIDAYU (Dayak–Malay–Chinese) context. Using an exploratory qualitative design, the research involved 18 participants aged 18–28 years from the service, retail, education, and MSME sectors in Pontianak, Singkawang, and Ketapang. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke’s thematic analysis, generating 138 codes, 24 subcategories, and three themes. The findings revealed three dominant adaptation patterns: communication adjustment, learning from senior workers, and seeking clarity and meaning in work. Organizational factors—particularly open leadership and flexible work structures–significantly facilitate adaptation, while authoritarian leadership and rigid structures hinder it. Peer support emerged as the strongest community factor accelerating Gen Z’s social adjustment, supported by multicultural workplace values fostering acceptance and comfort. The study concludes that Gen Z’s adaptation is an interactive, context-dependent process shaped by personal strategies, organizational culture, and social dynamics of TIDAYU communities. These insights emphasize that successful adaptation occurs when organizational values align with the generational needs and local cultural norms. The findings highlight the importance of adopting inclusive leadership, establishing flexible work systems, and strengthening cross-generational and cross-cultural engagement to enhance Gen Z integration and workplace harmony in multicultural regions.